Continued Moral Pressure for Responsible Globalization, Volume II : The G20 Interfaith Forum During Unsettled Times (2018-2023) - Christie, James Taylor,; Steiner, Sherrie M., (International Studies in Religion and Society ;, 2025)
If you are worried about the future of the earth and her inhabitants, then this book is for you. Authors from East and West document collaborative efforts that identify diverse faith-based ethical responses to global challenges. The history of this cosmopolitan fragile partnership with governments illuminates a positive pathway that affirms human rights and promotes sustainable solutions. We employ a new interfaith model built on the political philosophy of loyal opposition to demonstrate an openness to dissent and diversity as a way of cultivating trust. Contentious issues are addressed from climate change and geopolitics to human rights and religious freedom.